2021
DOI: 10.1007/s10884-020-09926-4
|View full text |Cite
|
Sign up to set email alerts
|

$$\mu $$-Norm and Regularity

Abstract: In [22] we introduce the concept of a µ-norm for a bounded operator in a Hilbert space. The main motivation is the extension of the measure entropy to the case of quantum systems. In this paper we recall the basic results from [22] and present further results on the µ-norm. More precisely, we specify three classes of unitary operators for which the µ-norm generates a bistochastic operator. We plan to use the latter in the construction of quantum entropy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This construction was proposed in [4]. In [4], it was shown that, for regular (see [16]) unitary operators on L 2 (T n , µ), where T n is the torus and µ is the Lebesgue measure on T n (d µ = (1/(2π) n )d x 1 . .…”
Section: Definition Of Entropymentioning
confidence: 99%
See 4 more Smart Citations
“…This construction was proposed in [4]. In [4], it was shown that, for regular (see [16]) unitary operators on L 2 (T n , µ), where T n is the torus and µ is the Lebesgue measure on T n (d µ = (1/(2π) n )d x 1 . .…”
Section: Definition Of Entropymentioning
confidence: 99%
“…In [4,15,16,17] the question was raised about defining a function h on the semigroup Iso(L 2 (X , µ)) of isometric operators such that the diagram End(X , µ) h ւ ց Koop…”
Section: Introduction and Main Definitionsmentioning
confidence: 99%
See 3 more Smart Citations